Answer:
a³ + b³
Step-by-step explanation:
Given
(a + b)(a² - ab + b²)
Each term in the second factor is multiplied by each term in the first factor, that is
a(a² - ab + b²) + b(a² - ab + b²) ← distribute both parenthesis
= a³ - a²b + ab² + a²b - ab² + b³ ← collect like terms
= a³ + b³
Mabye try making the triangle a right triangle and use SohCahToa (sin, cos, tan) to figure out each angle?
If A = (0,2,3,4,9,11), B = {2,3,6,8,9,10) and C= {0,2,3,9), then (A-B) n(A-C) is
timofeeve [1]
Answer:
(A-B)n(A-C) ={ }
<h3><em>hope</em><em> </em><em>it</em><em> </em><em>will</em><em> </em><em>help</em><em>.</em></h3>
<em>Wishing</em><em> </em><em>a</em><em> </em><em>nice</em><em> </em><em>day</em><em>.</em>
Equilateral triangle means each angle equals 60 degrees.
60 = 7x - 3
63 = 7x
x = 9
Answer:
Show questions
Step-by-step explanation:
common sense